Numerical Recovery of Gas Flows in Pipeline Systems - Vadim E. Seleznev (Journal of Applied Mathematics)
Optimal control, prevention and investigation of accidents, and detection of discrepancies in estimated gas supply and distribution volumes are relevant problems of trunkline operation. Efficient dealing with these production tasks is based on the numerical recovery of spacetime distribution of nonisothermal transient flow parameters of transmitted gas mixtures based on full-scale measurements in a substantially limited number of localities spaced considerable distances apart along the gas pipelines. The paper describes a practical method of such recovery by defining and solving a special identification problem. Simulations of product flow parameters in extended branched pipelines, involving calculations of the target function and constraint function for the identification problem of interest, are done in the 1D statement. In conclusion, results of practical application of the method in the gas industry are briefly discussed.